Urban Poetry, Private Morality, Postmodernist Realism… Luis García Montero (XXI Century. Spanish Literature and Culture, 2004)
Luis García Montero, revitalizes Spanish poetry through a new poetic generation of a realist andfigurative disposition that establish an identified subject between poet and city, a poetic voice which isclearly urban, closely linked with the world of affection. Additionally, we find the two sides of the samepoetic exercise: private morality against public ethics; a fight which entails a progressive utopia towardspostmodernist realism.
Keywords: Luis García Montero; García Montero; sentimentalism; postmodernism; realism